Porous carbon material, method for producing same, positive electrode containing carbon material as positive electrode active material, and lithium secondary battery
By using the porous carbon material treated by the activation process as the positive electrode active material in the lithium sulfur battery, and combining with the slightly soluble electrolyte (SSE) system, the problem of shortening the life of the lithium sulfur battery is solved, and a lithium secondary battery with high energy density and long life is realized.
Patent Information
- Application Number
- CN202380071805.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-16
- Filing Date
- 2023-12-14
- Publication Date
- 2025-05-06
AI Technical Summary
The life of lithium-sulfur batteries during charging and discharging is mainly due to side reactions in the electrolyte, instability of lithium metal and deposition of positive electrode by-products, which leads to the dissolution and shuttle of lithium polysulfide, reducing the capacity and life of the battery.
A porous carbon material that increases the pore volume and specific surface area through the activation process is used as the positive electrode active material, and a sulfur-carbon composite material is formed in combination with a slightly soluble electrolyte (SSE) system to improve the utilization rate of sulfur.
Through the application of enhanced porous carbon materials, the discharge capacity and life characteristics of lithium secondary batteries have been significantly improved, and the theoretical discharge capacity of more than 80% of sulfur can be effectively utilized to achieve a high energy density lithium sulfur battery.
Smart Images

Figure CN119947988A_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2022-0176685, filed on December 16, 2022, the disclosure of which is incorporated herein by reference in its entirety.
[0002] The present invention relates to a porous carbon material, a method for manufacturing the same, a positive electrode for a lithium secondary battery containing the carbon material as a positive electrode active material, and a lithium secondary battery itself. More specifically, the present invention relates to a porous carbon material, a method for manufacturing the same, and a positive electrode for a lithium secondary battery containing the carbon material as a positive electrode active material, wherein the carbon material has an increased pore volume and specific surface area through an activation process. By applying the porous carbon material to the positive electrode, the performance of a slightly soluble electrolyte (SSE) lithium secondary battery can be improved. Background Art
[0003] With applications ranging from mobile phones, tablets, laptops and cameras to energy sources for electric vehicles (EV) and hybrid electric vehicles (HEV), people are increasingly interested in energy storage technologies, leading to more research and development in electrochemical devices. The development of lithium-based secondary batteries such as lithium-sulfur batteries that can be charged and discharged has been the focus of attention. In recent years, the development of such batteries has led to the research and development of new electrode and cell designs to improve capacity density and specific energy.
[0004] These lithium-based secondary batteries (especially lithium-sulfur batteries) have high energy density (or theoretical capacity) and are becoming the next generation of secondary batteries that can replace lithium-ion batteries. In such lithium-sulfur batteries, a reduction reaction of sulfur and an oxidation reaction of lithium metal occur during discharge, and sulfur forms a linear structure of lithium polysulfide (LiPS) from a ring structure of S8, and such lithium-sulfur batteries are characterized by a stepwise discharge voltage until the polysulfide is completely reduced to Li2S.
[0005] However, the main obstacle to the commercialization of lithium-sulfur batteries is their lifespan, which is shortened during charge and discharge. The causes of this degradation include side reactions in the electrolyte (deposition of byproducts due to electrolyte decomposition), instability of lithium metal (growth of dendrites on the lithium anode, causing short circuits), and deposition of cathode byproducts (lithium polysulfide dissolution from the cathode).
[0006] In other words, in a battery using a sulfur compound as a positive electrode active material and an alkali metal such as lithium as a negative electrode active material, dissolution and shuttling of lithium polysulfide occurs during charge and discharge, and lithium polysulfide is transferred to the negative electrode, which reduces the capacity of the lithium-sulfur battery, thereby reducing the life of the battery and reducing its reactivity. In other words, polysulfide dissolved from the positive electrode has a high solubility in an organic electrolyte, which can lead to undesirable movement (PS shuttling) through the electrolyte to the negative electrode, resulting in a decrease in capacity due to irreversible loss of the positive electrode active material, and a shortened battery life due to deposition of sulfur particles on the surface of the lithium metal due to side reactions.
[0007] On the other hand, for lithium-sulfur batteries to achieve high energy density of more than 400 Wh / kg or more than 600 Wh / L, they require electrolytes and cathode active material systems that can operate under high load conditions (more than about 4.0 mAh / cm²) and low porosity (less than about 60%). Depending on the electrolyte, the behavior of such lithium-sulfur batteries varies significantly. Electrolytes in which sulfur in the cathode is dissolved in the form of lithium polysulfide (LiPS) are called cathode electrolytes. In contrast, electrolytes in which sulfur is rarely dissolved in the form of lithium polysulfide are called sparingly soluble electrolytes (SSEs). Conventional lithium-sulfur batteries using a cathode electrolyte system form Li2S x (Cathode electrolyte type) intermediate polysulfides rely on liquid phase reactions. Therefore, they fail to fully utilize the high theoretical discharge capacity of sulfur (1,675 mAh / g), and the dissolution of polysulfides further leads to rapid battery degradation and shortened life.
[0008] On the other hand, in recent years, an electrolyte system of a slightly soluble electrolyte (SSE) capable of suppressing the dissolution of polysulfides has been developed, and it has been confirmed that when a carbon material with a high BET specific surface area is used as a sulfur carrier, more than 80% of the theoretical discharge capacity of sulfur can be utilized. However, the high specific surface area of the carbon material used as a sulfur carrier does not necessarily lead to a high discharge capacity. In particular, in the case of a high sulfur content (e.g., >70 wt %), in addition to the specific surface area of the carbon material, the pore volume of the carbon material also has a significant effect on the utilization rate of sulfur. In order to realize a battery with a high energy density (e.g., >400 Wh / kg), it is necessary to use a high-load electrode with a positive active material having a high sulfur content, and therefore, it is necessary to optimize by controlling the specific surface area and porosity of the carbon material.
[0009] Therefore, in the case of basically using an SSE electrolyte system, by applying a carbon material for a positive electrode active material having an increased specific surface area and pore volume compared with conventional carbon materials, a battery having a high sulfur utilization rate even under a high sulfur content condition is required. Summary of the invention
[0010] [Technical issues]
[0011] Therefore, an object of the present invention is to provide a porous carbon material, a method for producing such a carbon material, a positive electrode for a lithium secondary battery comprising the carbon material as a positive electrode active material, and a lithium secondary battery itself, wherein the carbon material has an increased pore volume and specific surface area through an activation process. The present invention aims to improve the performance of a slightly soluble electrolyte (SSE) lithium secondary battery by applying an enhanced porous carbon material to a positive electrode.
[0012] [Technical solution]
[0013] In order to achieve the above object, the present invention provides a porous carbon material having a 2 / g and a surface area of 5 cm 3 / g or more pore volume.
[0014] The present invention also provides a method for manufacturing a porous carbon material, the method comprising the following steps: physically activating the carbon material with a gas activator; or chemically activating the carbon material with a chemical activator.
[0015] Furthermore, the present invention provides a positive electrode for a lithium secondary battery, which contains, as a positive electrode active material, a sulfur-carbon composite material in which sulfur is supported in a porous carbon material.
[0016] In addition, the present invention provides a lithium secondary battery, which includes: a positive electrode for a lithium secondary battery; a negative electrode; a separator therebetween; and an electrolyte, wherein the electrolyte includes: a first solvent containing a fluorine-containing ether compound, a second solvent containing a glycol diether compound, and a lithium salt.
[0017] [Beneficial Effects]
[0018] According to the present invention, a porous carbon material, a method for manufacturing the same, a positive electrode for a lithium secondary battery containing the carbon material as a positive electrode active material, and a lithium secondary battery itself provide the advantage of improving the performance of a slightly soluble electrolyte (SSE) lithium secondary battery. This is achieved by applying a porous carbon material having an increased pore volume and specific surface area through an activation process to the positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a nitrogen adsorption / desorption isotherm for determining the specific surface area of the porous carbon materials according to the examples and comparative examples of the present invention.
[0020] Figure 2 It is a pore size distribution diagram (BJH diagram, mesopore / macropore analysis) for determining the pore size of the porous carbon materials according to the examples of the present invention and the comparative examples.
[0021] Figure 3 It is a pore size distribution diagram (HK diagram, micropore analysis) for determining the pore size of the porous carbon materials according to the examples of the present invention and the comparative examples.
[0022] Figure 4 3 is a thermogravimetric analysis (TGA) graph of the sulfur-carbon composite material according to the embodiment of the present invention and the comparative example.
[0023] Figure 5 is a graph showing the discharge capacity of lithium secondary batteries according to Examples of the present invention and Comparative Examples.
[0024] Figure 6 is a graph showing the discharge capacity and life characteristics of lithium secondary batteries according to Examples of the present invention and Comparative Examples. DETAILED DESCRIPTION
[0025] Hereinafter, the present invention will be described in detail.
[0026] The porous carbon material according to the present invention has a thickness of 1,700 m 2 / g and a surface area of 5 cm 3 / g or more pore volume.
[0027] In order to achieve a high energy density of about 400 Wh / kg or more or 600 Wh / L or more for lithium-sulfur batteries, it is necessary to be able to store energy at high loads (about 4.0 mAh / cm 2 An electrolyte and positive electrode active material system operating under conditions of high porosity (about 60% or more) and low porosity (about 60% or less). In addition, in this electrolyte system, a slightly soluble electrolyte (SSE) system was developed, that is, to solve the problems associated with the positive electrode electrolyte by suppressing the dissolution of polysulfides (wherein the sulfur from the positive electrode is dissolved into the electrolyte in the form of lithium polysulfide (LiPS)). In addition, by applying a carbon material with a high BET (Brunauer-Emmett-Teller) specific surface area as a carrier of sulfur in the positive electrode active material and integrating it with the SSE electrolyte system, it was confirmed that more than 80% of the theoretical discharge capacity of sulfur can be utilized (this means that the utilization rate of sulfur is more than 80%), where "sulfur utilization rate" refers to the ratio of the discharge capacity (mAh) per gram of sulfur in the battery positive electrode to the theoretical capacity of sulfur 1,675 mAh / g. For example, if the discharge capacity of a lithium-sulfur battery per gram of sulfur in the cathode is 1,600 mAh / g, the utilization of sulfur is 95.5% (1,600 / 1,675).
[0028] However, the large specific surface area of the carbon material used as a sulfur carrier does not necessarily indicate a high discharge capacity. In particular, in the case of a high sulfur content (e.g., >70% by weight), in addition to the specific surface area of the carbon material, the pore volume of the carbon material also has a significant effect on the utilization rate of sulfur. Therefore, even if the specific surface area of the carbon material is large, if the pore volume is small, there are not enough holes to load sulfur, resulting in low sulfur loading efficiency, which reduces the electron acceptance of non-conductive sulfur and increases the proportion of sulfur involved in the reaction, which greatly reduces the discharge capacity and life characteristics of the battery. In other words, in order to achieve a battery with a high energy density (e.g., >400 Wh / kg), it is necessary to use a high-load electrode by applying a positive active material with a high sulfur content, and it is necessary to optimize by controlling the specific surface area and porosity of the carbon material. Therefore, the applicant has invented a carbon material for a positive active material, which has an increased specific surface area and pore volume compared to an existing carbon material, and is also combined with an SSE electrolyte system to improve the performance of the battery.
[0029] The present invention has 1,700 m 2 / g and a surface area of 5 cm 3 A porous carbon material having a pore volume of 0.1 / g or more is a porous carbon material treated with an activator and is used as a positive electrode active material in a lithium secondary battery having a sparingly soluble electrolyte (SSE) electrolyte system.
[0030] In other words, while existing methods use carbonized porous carbon materials, carbonizing such materials results in the removal of organic matter other than carbon (C), which makes it difficult to produce additional micropores in the porous carbon material. However, the present invention forms micropores by physically activating the porous carbon material with a gas activator or chemically activating the porous carbon material with a chemical activator, thereby gasifying the carbon in a solid phase while the carbon reacts with the gas or chemical. However, the present invention is characterized in that no additional carbonization process is performed during the physical activation or chemical activation. Therefore, the porous carbon material of the present invention is a carbon material that has been activated with an activator, but no additional carbonization process (or treatment) is performed during the activation process (or treatment).
[0031] In addition, the porous carbon material of the present invention shows the maximum effect when used with an SSE (slightly soluble electrolyte) electrolyte system as a positive electrode active material in a lithium secondary battery, and it can utilize more than 80% of the theoretical discharge capacity of sulfur. Therefore, when used as a positive electrode active material in a lithium secondary battery with an SSE electrolyte system, rather than being used with a conventional electrolyte (positive electrode electrolyte) in a lithium secondary battery, the porous carbon material of the present invention can maximize the performance of the battery. In other words, the porous carbon material is characterized in that it is used as a positive electrode active material in a lithium secondary battery, and the lithium secondary battery comprises an electrolyte, and the electrolyte comprises: a first solvent containing a fluorine-containing ether compound, a second solvent containing a glycol diether compound, and a lithium salt.
[0032] The porous carbon material of the present invention has a 2 / g or more. If the porous carbon material has a specific surface area of less than 1,700 m 2 / g of specific surface area, the sulfur loading efficiency is low and the electrode side reactions are large, resulting in a charging overvoltage phenomenon, which greatly reduces the discharge capacity and life characteristics of the battery.
[0033] In addition, the porous carbon material of the present invention has a 5 cm 3 / g or more, preferably 7 cm 3 / g or more, more preferably 7 to 10 cm 3 / g pore volume. If the porous carbon material has a pore volume less than 5 cm 3 / g of pore volume, the sulfur loading efficiency is reduced (i.e., the sulfur loading amount is reduced), and this may lead to the problem that the electron accepting ability of non-conductive sulfur is reduced and the proportion of sulfur participating in the reaction is increased, thereby significantly reducing the discharge capacity and life characteristics of the battery. Therefore, if the porous carbon material has a pore volume of 7 cm 3 / g or more, then the pore volume is less than 7 cm 3 On the other hand, although the present invention focuses on the application of porous carbon materials in batteries, it is obvious that the present invention can be used in other fields requiring porous carbon materials besides batteries.
[0034] As mentioned above, with 1,700 m 2 / g and a surface area of 5 cm 3 The porous carbon material of the present invention having a pore volume of 1,700 m / g or more can be, for example: carbon nanotubes; graphene (particularly multilayer graphene sheets, MGF); graphite; carbon black materials such as carbon black, acetylene black, Ketjen black, Danka black, thermal black, channel black, furnace black, lamp black, etc.; carbon fiber; or a mixture containing two or more of the foregoing substances. In addition, among these substances, those having a pore volume of 1,700 m / g or more are preferred in terms of improving the performance of the battery. 2 / g and a surface area of 5 cm 3 Ketjen black having a pore volume of 1000 Å / g or more may be the most advantageous.
[0035] Hereinafter, a method for manufacturing the porous carbon material will be described. The method for manufacturing the porous carbon material, i.e., the method for manufacturing the porous carbon material, comprises the steps of physically activating the carbon material with a gas activator or chemically activating the carbon material with a chemical activator. In addition, the method is characterized in that no additional carbonization process is performed during the physical activation or chemical activation.
[0036] The carbon material may be any one of the following: carbon nanotubes; graphene (particularly multi-layer graphene sheets, MGF); graphite; carbon black materials such as carbon black, acetylene black, Ketjen black, Danka black, thermal black, channel black, furnace black, lamp black, etc.; carbon fiber; and a mixture comprising two or more of the foregoing substances. In addition, the activated carbon material may be a carbon material that has not undergone any carbonization treatment other than the activation treatment, that is, no additional carbonization process is performed during physical or chemical activation, and no carbonization process is performed before or after activation.
[0037] In the past, only carbonized carbon materials were used, and because carbonization only removed organic matter other than carbon (C), it was difficult to form additional micropores in the carbon material. However, if the carbon material is physically activated with a gas activator or chemically activated with a chemical activator, additional micropores can be formed in the carbon material by a gasification process of solid carbon while the carbon material reacts with the gas or chemical.
[0038] Therefore, the method for manufacturing a porous carbon material of the present invention includes the following steps: activating the carbon material using an activator, wherein no additional carbonization process is performed during the physical activation or chemical activation, and no carbonization process is performed before or after the activation treatment (physical activation or chemical activation).
[0039] Below, the physical activation method and the chemical activation method will be described in detail. First, the physical activation method is a method of activation at high temperature using a gas activator (or activation gas). Examples of such gas activators include water vapor (steam), carbon monoxide (CO), carbon dioxide (CO2) and oxygen (O2). In the case of the above-mentioned physical activation method, the activation temperature can be 500 to 1,000°C, preferably 800 to 1,000°C. In addition, the activation time in this case can be 1 to 10 hours, preferably 3 to 10 hours. If the above-mentioned activation temperature and time range are exceeded, micropores may not be formed normally in the carbon material.
[0040] The above-mentioned chemical activation method is a method of using a chemical activator to activate at high temperature, and when the chemical activator is deposited on the carbon material and heated, the dehydration and oxidation reaction of the chemical is carried out, and micropores can be formed in the porous carbon material. Examples of such chemical activators include KOH, K2CO3, NaOH, Na2CO3, AlCl3, MgCl3 and H3PO4, which are compounds with strong dehydration and oxidation properties. The porous carbon material can be purged with an inert gas such as nitrogen (N2), argon, etc. before chemical activation, and there is no particular restriction on the injection conditions of the inert gas. In addition, a sealed container can be used for chemical activation, and this sealed container can be a glass jar or other conventional containers that can be sealed and purged even if an inert gas is injected.
[0041] The deposition ratio of the carbon material to the chemical activator before activation may be 1:8 to 1:1 by weight. In the case of the above chemical activation method, the activation temperature may be 400 to 1,000° C., preferably 500 to 900° C. The activation time may be 1 to 10 hours, preferably 1 to 5 hours. If the above activation temperature and time ranges are exceeded, micropores may not be normally formed in the porous carbon material.
[0042] Next, the positive electrode for a lithium secondary battery of the present invention is described. The positive electrode for a lithium secondary battery comprises a sulfur-carbon composite material ((C2S x ) n :x=2.5 to 50, n≥2), wherein sulfur is loaded on the porous carbon material as the positive electrode active material described previously. In addition, in addition to the positive electrode active material, the positive electrode for lithium secondary battery also contains a binder and a conductive material. Sulfur can be elemental sulfur (S8), a sulfur compound or a mixture thereof, and the sulfur compound can specifically be Li2S n (n≥1) or organic sulfur compounds.
[0043] The particle size of the sulfur-carbon composite material can be between 1 and 100 μm. If the particle size of the sulfur-carbon composite material is less than 1 μm, the resistance between the particles will increase, which may cause overvoltage in the lithium-sulfur battery electrode. If it exceeds 100 μm, the surface area per unit weight is reduced, thereby reducing the wetting area with the electrolyte and the reaction site with the lithium ions in the electrode. In addition, as the amount of electron transfer relative to the size of the composite material becomes smaller, the reaction slows down, which may lead to a decrease in the battery discharge capacity.
[0044] The content of sulfur contained in the positive electrode may be 60 to 90 wt %, preferably 65 to 85 wt %, and more preferably 70 to 80 wt %, based on the total weight of the positive electrode. If sulfur is used in an amount less than 60 wt % of the total weight of the positive electrode, a decrease in battery energy density may occur, and if sulfur is used in an amount greater than 90 wt %, a decrease in electrode conductivity and a decrease in electrode stability may occur.
[0045] The content of the positive electrode active material containing sulfur and carbon material may be 80 to 99 parts by weight, preferably 90 to 95 parts by weight, relative to 100 parts by weight of the total weight of the positive electrode. If the content of the positive electrode active material is less than 80 parts relative to 100 parts by weight of the total weight of the positive electrode, the energy density of the battery may be reduced, and if the content of the positive electrode active material exceeds 99 parts relative to 100 parts by weight of the total weight of the positive electrode, the conductivity in the electrode may be reduced and the stability of the electrode may be reduced.
[0046] The binder contained in the positive electrode helps to combine the positive electrode active material and the conductive material, and helps to be bonded to the current collector. The example of the binder can include polyvinylidene fluoride (PVdF), a copolymer of polyvinylidene fluoride and polyhexafluoropropylene (PVdF / HFP), polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, polymethyl (meth) acrylate, polyethyl (meth) acrylate, polytetrafluoroethylene (PTFE), polyvinyl chloride, polyacrylonitrile, polyvinyl pyridine, polyvinyl pyrrolidone, styrene-butadiene rubber, nitrile rubber, ethylene propylene diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butene rubber, fluororubber, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose and mixtures thereof. However, the use of these materials is not limited to these examples.
[0047] Based on 100 parts by weight of the total weight of the positive electrode, the amount of the binder added is generally 1 to 50 parts by weight, preferably 3 to 15 parts by weight. A binder content of less than 1 part by weight may result in insufficient adhesion of the positive electrode active material to the current collector, while a binder content of more than 50 parts by weight may result in improved adhesion but a corresponding reduction in the positive electrode active material, thereby resulting in a decrease in battery capacity.
[0048] There is no particular restriction on the conductive material contained in the positive electrode, as long as it has excellent conductivity while not causing side reactions or chemical changes in the battery environment. Generally, graphite or conductive carbon can be used. Examples include: natural graphite, artificial graphite; carbon black materials such as carbon black, acetylene black, Ketjen black, Danka black, thermal black, channel black, furnace black, lamp black; carbonaceous materials with a crystal structure of graphene or graphite; carbon nanotubes; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. These substances can be used alone or in combination of two or more, but the use is not limited to these examples.
[0049] Based on 100 parts by weight of the total weight of the positive electrode, the amount of the conductive material added may be 0.5 to 10 parts by weight, preferably 0.5 to 5 parts by weight, but the conductive material may not be included in the positive electrode of the present invention. If the content of the conductive material is too high, exceeding 10 parts by weight, based on 100 parts by weight of the total weight of the positive electrode, the amount of the positive electrode active material may be relatively small, resulting in reduced capacity and energy density. There is no particular limitation on the method for incorporating the conductive material into the positive electrode, and any method known in the art can be used, such as coating the positive electrode active material. In addition, if necessary, a conductive second coating layer may be added to the positive electrode active material instead of adding the above-mentioned conductive material.
[0050] In addition, a filler may be optionally added to the positive electrode of the present invention as a component to inhibit its expansion. There is no particular limitation on such a filler, as long as it can inhibit the expansion of the electrode without causing chemical changes in the battery, and for example, oligomers such as polyethylene and polypropylene; fibrous materials such as glass fiber and carbon fiber, etc. can be used.
[0051] The positive electrode can be manufactured by dispersing the positive electrode active material, the binder and the conductive material in a dispersant (solvent) and mixing to form a slurry, applying the slurry to the positive electrode collector, and then drying and rolling. The dispersant may include but is not necessarily limited to N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, isopropanol, water, and mixtures thereof.
[0052] For the current collector of the positive electrode, materials such as platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), aluminum (Al), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), ITO (indium doped SnO2), FTO (fluorine doped SnO2) and alloys thereof can be used. In addition, aluminum (Al) or stainless steel surface treated with carbon (C), nickel (Ni), titanium (Ti) or silver (Ag) can also be used, but the selection is not limited to these materials. The positive electrode current collector can be in the form of foil, film, sheet, punching body, porous body, foam body, etc.
[0053] Finally, the lithium secondary battery according to the present invention is described. As described above, the lithium secondary battery comprises a positive electrode for a lithium secondary battery, a negative electrode, a separator therebetween, and an electrolyte, wherein the electrolyte comprises: a lithium salt, a first solvent containing a fluorine-containing ether compound, and a second solvent containing a glycol diether compound. In addition, when sulfur is contained in the positive electrode for a lithium secondary battery, the lithium secondary battery is a lithium-sulfur battery.
[0054] The lithium secondary battery of the present invention comprises a slightly soluble electrolyte (SSE) and a positive electrode active material having a 1,700 m 2 / g and a surface area of 5 cm 3 The porous carbon material having a pore volume of 100 Wh / kg or more can have a high energy density of about 400 Wh / kg or more or 600 Wh / L or more while the utilization rate of sulfur can be 80% or more, preferably 85% or more of the theoretical discharge capacity.
[0055] Hereinafter, a first solvent containing a fluorine-containing ether compound, a second solvent containing a glycol diether-based compound, and a lithium salt contained in an electrolyte of a lithium secondary battery according to the present invention will be described in detail.
[0056] The first solvent is an electrolyte solvent containing a fluorinated ether compound, which has the effect of dissolving polysulfide and inhibiting solvent decomposition, thereby improving the coulombic efficiency (CE) of the battery, and ultimately improving the life of the battery. More specifically, compared with general organic solvents containing alkanes, the first solvent containing the above-mentioned fluorinated ether compound has excellent structural stability of the solvent due to fluorine substitution, and is highly stable. Therefore, using it in the electrolyte of a lithium secondary battery can greatly improve the stability of the electrolyte, thereby improving the life performance of the lithium secondary battery.
[0057] Examples of the fluorine-containing ether compound include one or more hydrofluoroether (HFE) type compounds selected from the group consisting of 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), bis(fluoromethyl) ether, 2-fluoromethyl ether, bis(2,2,2-trifluoroethyl) ether, propyl 1,1,2,2-tetrafluoroethyl ether, isopropyl 1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl isobutyl ether, 1,1,2,3,3,3-hexafluoropropyl ethyl ether, 1H,1H,2'H,3H-decafluorodipropyl ether and 1H,1H,2'H-perfluorodipropyl ether.
[0058] The second solvent containing a glycol diether compound (but not containing fluorine) is used as an electrolyte solvent. It not only dissolves the lithium salt to provide lithium ion conductivity to the electrolyte, but also plays a role in dissolving the positive electrode active material sulfur to promote the electrochemical reaction with lithium.
[0059] The specific example of glycol diether compounds comprises one or more selected from the following: dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether (diethylene glycol dimethyl ether), diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether (triethylene glycol dimethyl ether), triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether (tetraethylene glycol dimethyl ether), tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether and polyethylene glycol methyl ethyl ether. This list is not complete, wherein, dimethoxyethane can be preferably used.
[0060] The lithium salt used as the electrolyte salt to improve the ion conductivity may be any one commonly used in industry without limitation. Specific examples of the lithium salt include one or more selected from the following: LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium salts of lower aliphatic carboxylic acids having less than 4 carbon atoms, lithium tetraphenylborate and lithium imide.
[0061] The concentration of the lithium salt can be determined by considering ion conductivity and the like, and may be, for example, 0.1 to 2 M, preferably 0.5 to 1 M, more preferably 0.5 to 0.75 M, etc. If the concentration of the lithium salt is less than the above range, it may be difficult to ensure ion conductivity suitable for driving the battery, and if it exceeds the above range, the viscosity of the electrolyte may increase, thereby reducing the mobility of lithium ions, or the decomposition reaction of the lithium salt itself may increase, thereby reducing the performance of the battery.
[0062] In the electrolyte containing the first solvent, the second solvent and the lithium salt as described above, the molar ratio of the lithium salt, the second solvent and the first solvent may be 1:0.5 to 3:4.1 to 15. In addition, in the example of the present invention, the molar ratio of the lithium salt, the second solvent and the first solvent may be 1:2:4 to 13 or 1:3:3 to 10 or 1:4:5 to 10, so that in the electrolyte contained in the lithium secondary battery of the present invention, the first solvent containing the fluorine-containing ether compound may be included at a higher content ratio than the second solvent containing the glycol diether compound. In this way, when the first solvent containing the fluorine-containing ether compound is included at a higher content ratio than the second solvent containing the glycol diether compound, it is advantageous in suppressing the generation of polysulfides, enabling a battery capacity close to the theoretical capacity of sulfur, and suppressing the reduction of the battery capacity when the battery is used. Therefore, it is preferred that the first solvent containing the fluorine-containing ether compound is included at a higher content ratio than the second solvent containing the glycol diether compound.
[0063] The negative electrode included in the lithium secondary battery of the present invention is a lithium metal, and may also be included in a negative electrode collector on one side of the lithium metal. The negative electrode collector may be selected from, but not limited to, copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, alloys thereof, and combinations thereof, provided that it has high conductivity and does not cause chemical changes in the battery. Stainless steel may be surface treated with carbon, nickel, titanium or silver. As alloys, aluminum-cadmium alloys and calcined carbon, non-conductive polymers treated with conductive materials, or conductive polymers may be used. Typically, copper foil is used as a negative electrode collector.
[0064] In addition, the form may be a film, sheet, foil, net, porous body, foamed body, nonwoven fabric body, etc. having fine concavoconvex / concave formed / not formed on its surface. In addition, the thickness of the negative electrode current collector may be in the range of 3 to 50 μm. If the thickness of the negative electrode current collector is less than 3 μm, the current collection effect is reduced, and if the thickness exceeds 50 μm, when the battery is assembled by folding, the processability is reduced.
[0065] The lithium metal may be lithium or a lithium alloy. The lithium alloy may include an element capable of forming an alloy with lithium, specifically an alloy of lithium with one or more species selected from the group consisting of Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al.
[0066] The lithium metal may be in the form of sheets or foils, and in some cases, for example, lithium or lithium alloys on current collectors may be deposited or coated by dry processes, or metals and alloys on particles may be deposited or coated by wet processes.
[0067] A conventional separator may be interposed between the positive electrode and the negative electrode. The separator is a physical barrier for physically separating the electrodes. It can be any commonly used separator without particular limitation, and is particularly desirable to have low resistance to ion movement of the electrolyte and excellent electrolyte wettability.
[0068] In addition, the separator allows lithium ions to be transported between the positive electrode and the negative electrode while separating or insulating the positive electrode and the negative electrode from each other. Such a separator can be made of a porous, non-conductive or insulating material. The separator can be a separate component such as a membrane or a coating added to the positive electrode and / or the negative electrode.
[0069] Examples of polyolefin porous films that can be used as separators include films formed by the following substances alone or in combination: polyethylene such as high-density polyethylene, linear low-density polyethylene, low-density polyethylene, ultra-high molecular weight polyethylene; and polyolefin polymers such as polypropylene, polybutylene, polypentene. Examples of non-woven fabrics that can be used as separators are polyphenylene ether, polyimide, polyamide and polycarbonate, polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate and polyphenylene sulfide, polyacetal, polyether sulfone, polyether ether ketone, polyester, etc., alone or in combination, and such non-woven fabrics can be in the form of fibers forming porous fabrics, including spunbond or melt-blown forms containing long fibers.
[0070] The thickness of the separator is not particularly limited, but is preferably in the range of 1 to 100 μm, more preferably in the range of 5 to 50 μm. If the thickness of the separator is less than 1 μm, the mechanical properties cannot be maintained, and if it exceeds 100 μm, the separator acts as a resistance layer and the performance of the battery is reduced. The pore size and porosity of the separator are not particularly limited, but the pore size is preferably 0.1 to 50 μm and the porosity is preferably 10% to 95%. When the pore size of the separator is less than 0.1 μm or when the porosity is less than 10%, the separator acts as a resistance layer, and when the pore size exceeds 50 μm or the porosity exceeds 95%, the mechanical properties cannot be maintained.
[0071] The lithium secondary battery of the present invention including the positive electrode, the negative electrode, the separator, and the electrolyte as described above can be manufactured through a process in which the positive electrode is placed facing the negative electrode, the separator is interposed therebetween, and the electrolyte is injected.
[0072] On the other hand, the lithium secondary battery according to the present invention can be applied to a battery cell used as a power source for a small device, and is particularly suitable as a unit cell in a battery module for a power source for a medium or large device. In this regard, the present invention also provides a battery module comprising two or more lithium secondary batteries electrically connected (in series or in parallel). Of course, the number of lithium secondary batteries contained in the battery module can be changed in view of the purpose and capacity of the battery module. In addition, the present invention provides a battery pack electrically connected to the battery module according to conventional techniques in the art. The battery module and the battery pack can be used to power one or more medium and large devices, including but not limited to: power tools; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV) and plug-in hybrid electric vehicles (PHEV); electric trucks; electric commercial vehicles; or power storage systems. However, it may be preferred that the lithium secondary battery of the present invention is a battery for an aircraft for urban air traffic (UAM).
[0073] Preferred Implementation
[0074] To illustrate the present invention, embodiments of the present invention will be described below, but it will be apparent to those skilled in the art that various changes and modifications may be accomplished within the scope of the present invention and technical ideas, and these changes and modifications are within the scope of the appended patent claims.
[0075] [Example 1] Fabrication of porous carbon materials
[0076] 20 g of Ketjen black was placed in a quartz tube using a fluidized bed reactor, purged with nitrogen for 1 minute, and then activated with CO2 gas at a temperature of 900°C for 5 hours.
[0077] [Comparative Example 1] Porous carbon materials
[0078] The same Ketjen black as used in Example 1 was prepared, but no activation treatment was performed.
[0079] [Experimental Example 1] Evaluation of specific surface area and pore volume of porous carbon materials
[0080] The specific surface area and pore volume of each porous carbon material in Example 1 and Comparative Example 1 were measured, and the results are shown in the following Table 1. The measurement was performed using a porosity analyzer (model: Belsorp-max, manufacturer: Bel Japan), and the values of the specific surface area and pore volume were obtained based on the nitrogen adsorption / desorption isotherm at 77 K.
[0081]
[0082] Figure 1 is a nitrogen adsorption / desorption isotherm for determining the specific surface area of the porous carbon materials according to the embodiments and comparative examples of the present invention, Figure 2 is a pore size distribution diagram (BJH diagram, mesopore / macroporous analysis) for determining the pore size of the porous carbon materials according to the embodiments of the present invention and the comparative examples, and Figure 3 is a pore size distribution diagram (HK diagram, micropore analysis) for determining the pore size of the porous carbon materials according to the embodiments of the present invention and the comparative examples. As shown in Table 1 and Figures 1 to 3 As shown in , as the results of measuring the specific surface area and pore volume of each porous carbon material of Example 1 and Comparative Example 1, it can be seen that compared with the porous carbon material of Comparative Example 1 that has not been activated, the specific surface area and pore volume of the activated porous carbon material of Example 1 are significantly increased.
[0083] [Experimental Example 2] Measurement of tap density of porous carbon materials
[0084] The tap density of each porous carbon material in Example 1 and Comparative Example 1 was measured, and the results are shown in the following Table 2. The results of 1,000 taps of a 100 ml sample using a tap density tester (model: KYT-5000K, manufacturer: SEISHIN) are shown below.
[0085]
[0086] As shown above, the tap density of each porous carbon material of Example 1 and Comparative Example 1 was measured. As shown in Table 2, the activated porous carbon material of Example 1 exhibited a lower tap density than the unactivated porous carbon material of Comparative Example 1. Therefore, the benefit of activating the carbon material can be seen.
[0087] [Example 2, Comparative Example 2] Manufacturing of sulfur-carbon composite materials
[0088] In order to ensure that sulfur was contained in each porous carbon material of Example 1 and Comparative Example 1, sulfur and the porous carbon material were mixed at a weight ratio of 70:30 and then heated to produce a sulfur-carbon composite material.
[0089] [Comparative Example 3] Manufacturing of sulfur-carbon composite materials
[0090] In order to ensure that the porous carbon material of the above-mentioned Comparative Example 1 contains sulfur, sulfur and the porous carbon material are mixed at a weight ratio of 60:40 and then heated to produce a sulfur-carbon composite material.
[0091] [Experimental Example 2] Thermogravimetric analysis (TGA) of sulfur-carbon composites
[0092] The sulfur-carbon composite materials prepared in Example 2, Comparative Example 2 and Comparative Example 3 were subjected to thermogravimetric analysis (temperature rise condition of 10°C / min (20°C to 900°C), air atmosphere), and the results of observing the respective mass changes are shown in FIG. Figure 4 On the other hand, thermogravimetric analysis was performed using a thermogravimetric analyzer (manufacturer: Mettler-Toledo).
[0093] Figure 4 2 is a thermogravimetric analysis (TGA) diagram of the sulfur-carbon composite material according to the embodiment of the present invention and the comparative example. The sulfur-carbon composite materials prepared in the embodiment 2, the comparative example 2 and the comparative example 3 were subjected to thermogravimetric analysis. Figure 4 As shown in , it can be seen that in Example 2, the volatilization of sulfur occurs at a relatively higher temperature due to the sulfur being loaded in the pores of the carbon material compared to Comparative Examples 2 and 3. This indicates that the activation treatment of the carbon material increases the loading efficiency of sulfur.
[0094] [Example 3] Manufacturing of lithium secondary batteries
[0095] Cathode Manufacturing
[0096] 90 parts by weight of the sulfur-carbon composite material prepared in Example 2 as a positive electrode active material (the content of sulfur alone was 63% by weight relative to the total weight of the positive electrode), 5 parts by weight of Danka black as a conductive material, and 5 parts by weight of styrene-butadiene rubber / carboxymethyl cellulose (SBR:CMC=7:3) were mixed to prepare a positive electrode slurry composition, and then the slurry composition prepared above was coated on a current collector (Al foil), dried at 50° C. for 12 hours, and pressed with a roller press to prepare a positive electrode (wherein the sulfur loading was 3.0 mAh / cm 2 ).
[0097] Electrolyte manufacturing
[0098] First, a sparingly soluble electrolyte (SSE) was prepared by mixing LiTFSI (concentration: 0.65 M), dimethoxyethane (second solvent), and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE, first solvent) in a molar ratio of 1:2:9 at room temperature.
[0099] Manufacturing of lithium secondary batteries
[0100] A coin cell type lithium secondary battery was manufactured by placing the above-made positive electrode face to face with a 150 μm thick lithium metal negative electrode, inserting a polyethylene (PE) separator therebetween, and injecting the above-made slightly soluble electrolyte (SSE). In the manufacture of the above-mentioned battery, the positive electrode was used as a Φ14 circular electrode, the polyethylene separator was used as Φ19, and the lithium metal was used as Φ16.
[0101] [Comparative Example 4] Manufacturing of lithium secondary batteries
[0102] A coin cell type lithium secondary battery was manufactured in the same manner as in Example 3, except that the sulfur-carbon composite material used was the sulfur-carbon composite material manufactured in Comparative Example 2 instead of the sulfur-carbon composite material manufactured in Example 2. The content of sulfur alone was 63% by weight of the total weight of the positive electrode.
[0103] [Comparative Example 5] Manufacturing of lithium secondary batteries
[0104] A coin cell type lithium secondary battery (the content of sulfur alone is 54 weight % of the total weight of the positive electrode) was manufactured in the same manner as in Example 3, except that the sulfur-carbon composite material used was the sulfur-carbon composite material manufactured in Comparative Example 3 instead of the sulfur-carbon composite material manufactured in Example 2.
[0105] [Experimental Example 3] Evaluation of discharge capacity and life characteristics of lithium secondary batteries
[0106] The lithium secondary batteries manufactured in Example 3, Comparative Example 4 and Comparative Example 5 were subjected to 0.1C charge / 0.1C discharge for three cycles and then 0.2C charge / 0.3C discharge, and their discharge capacity and life characteristics were evaluated. The discharge capacity evaluation results are shown in Table 3. The voltage range for the evaluation was 1.2 to 3.6 V, and the evaluation was performed at room temperature. Figure 5 is a graph showing the discharge capacity of lithium secondary batteries according to an embodiment of the present invention and a comparative example, and Figure 6 is a graph showing the discharge capacity and life characteristics of lithium secondary batteries according to Examples of the present invention and Comparative Examples.
[0107]
[0108] When the discharge capacity and life of the lithium secondary batteries manufactured in Example 3, Comparative Example 4, and Comparative Example 5 were measured, it was found that the sulfur-carbon composite material contained a carbon nanotube with a specific surface area of more than 1,700 m 2 / g and the pore volume is greater than 5 cm 3 The battery of Example 3, which contains 200 g of carbon material and uses SSE electrolyte, exhibits a discharge capacity exceeding 80% of the theoretical capacity despite having a high sulfur content of 63% based on the total weight of the positive electrode, as shown in Table 3 and Figure 5 and Figure 6 It was also found that the lifespan characteristics were high.
[0109] In contrast, compared with Example 3, the sulfur-carbon composite material includes a specific surface area of less than 1,700 m 2 / g and the pore volume is less than 5 cm 3 Although the batteries of Comparative Examples 4 and 5 with a carbon material of 0.1 g / cm2 were prepared using SSE electrolyte, they were found to be inferior in discharge capacity and life characteristics, as shown in Table 3 and Table 4. Figure 5 and Figure 6 In particular, in Comparative Example 4, despite having the same high sulfur content of 63% based on the total weight of the positive electrode as in Example 3, the high sulfur content has an adverse effect on the battery, resulting in significant overvoltage, resulting in reduced discharge capacity and nominal voltage, and reduced life characteristics.
Claims
1. A porous carbon material having a 2 / g and a surface area of 5 cm 3 / g or more pore volume.
2. The porous carbon material according to claim 1, wherein The porous carbon material has a 7 cm 3 / g or more pore volume.
3. The porous carbon material according to claim 1, wherein The porous carbon material is selected from: carbon nanotubes; graphene (multilayer graphene sheets, MGF); graphite; carbon black materials selected from carbon black, acetylene black, Ketjen black, Danka black, thermal black, channel black, furnace black and lamp black; carbon fiber; and a mixture containing two or more thereof.
4. The porous carbon material according to claim 3, wherein The porous carbon material is Ketjen black.
5. The porous carbon material according to claim 1, wherein The porous carbon material is activated.
6. The porous carbon material according to claim 1, wherein The porous carbon material is used as a positive electrode active material in a lithium secondary battery, The lithium secondary battery includes an electrolyte, wherein the electrolyte includes: a first solvent including a fluorine-containing ether compound; a second solvent including a glycol diether compound; and a lithium salt.
7. A method for manufacturing the porous carbon material according to claim 1, the method comprising the following steps: Physically activating the carbon material with a gas activator; or The carbon material is chemically activated using a chemical activating agent.
8. The method for producing a porous carbon material according to claim 7, wherein: The carbon material is reacted with a gas or a chemical to gasify carbon in a solid phase before the activation, thereby forming micropores in the carbon material.
9. The method for producing a porous carbon material according to claim 7, wherein: No carbonization process is performed during the physical activation or the chemical activation.
10. The method for producing a porous carbon material according to claim 7, wherein: No carbonization process is performed before or after the physical activation or the chemical activation.
11. The method for producing a porous carbon material according to claim 7, wherein: The gas activator is selected from the group consisting of water vapor, carbon monoxide, carbon dioxide and oxygen, and The physical activation using the gas activating agent is performed at a temperature of 500° C. to 1,000° C. for 1 to 10 hours.
12. The method for producing a porous carbon material according to claim 7, wherein: The chemical activator is selected from the group consisting of KOH, K2CO3, NaOH, Na2CO3, AlCl3, MgCl3 and H3PO4, and Wherein, the chemical activation using the chemical activating agent is performed at a temperature of 400° C. to 1,000° C. for 1 hour to 10 hours.
13. The method for producing a porous carbon material according to claim 7, wherein: The deposition ratio of the carbon material to the chemical activating agent before activation is 1:8 to 1:1 by weight. 14 . A positive electrode for a lithium secondary battery, comprising a sulfur-carbon composite material as a positive electrode active material, wherein sulfur is supported in the porous carbon material according to claim 1 .
15. A lithium secondary battery, comprising: the positive electrode for lithium secondary battery according to claim 14; a negative electrode; a separator interposed therebetween; and an electrolyte, The electrolyte comprises: a first solvent containing a fluorine-containing ether compound, a second solvent containing a glycol diether compound, and a lithium salt.
16. The lithium secondary battery according to claim 15, wherein: The content of sulfur contained in the positive electrode is 60 wt % to 90 wt % relative to the total weight of the positive electrode.
17. The lithium secondary battery according to claim 15, wherein: The utilization rate of sulfur contained in the positive electrode is more than 80% of the theoretical discharge capacity.